Formulación y aceptabilidad sensorial de pan enriquecido con pulpa de rábano (Raphanus sativus) - Mori Bernales, Litto (2024)
Radish (Raphanus sativus) is a cruciferous plant with great nutritional and medicinal benefits; however, many people do not consume it due to its pungent taste. Therefore, the objective of this research was to formulate a bread enriched with radish pulp and determine its acceptance by consumers. Likewise, the breads were characterized in terms of their moisture content, protein, lipids, iron, potassium and vitamin C. Three types of bread formulations were made with radish pulp, F1 (30%), F2 (50%), and F3 (60%). The results indicate that the three formulations have a great acceptability with relatively similar distributions regarding the qualification of the flavor, color and Texture attributes. However, in the odor attribute, F2 differed from the other two formulations. Being that the bread to which 50% radish pulp was added, was the one that showed the greatest acceptance by the panelists. Regarding the physicochemical analysis, it was observed that the addition of radish pulp to the breads increased the content of vitamin C, iron and potassium. In turn, the results of the microbiological analyzes demonstrated that the breads are safe for human consumption. We can conclude that radish pulp breads are an excellent option to improve the nutritional profile of breads that are consumed daily. Therefore, they would bring great benefits to people's health.